Mikalojaus Daukšos Postilės aliatyvas - Žilinskaitė, Eglė (Baltistica, 2010)
THE ALLATIVE CASE IN MIKALOJUS DAUKŠA’S Postilla A semantic analysis of the allative case in Daukša’s Postilla (1599) is performed in order to discuss various types of its use. The following 12 functions of allative are distinguished, which reflect well-established patterns of grammaticalization of goal-marking morphemes (Rice et al. 2007). I. Spatial functions. 1.1. Inanimate Goal of motion. The movement of the Figure (a verb of motion) is directed to the Goal expressed by the allative. This is the most basic meaning of the allative, e.g. Luke 24,28: du iǯg mokitiniu […] priârtinos miéſteloṕ kuríoṕ êio 18931, Dwá ʒ vcniow […] prʒybliyli ſido miáſtecká / do ktorego ßli 19811, ‘And they drew nigh unto the village, whither they went’. 1.2. Goal of motion, when the Figure acquires a location in physical proximity to the Goal, e.g. Luke 24,24: Ir nuêío nêkurie iġ mûſ grâbo 18925, Y chodʒili niektorʒy ʒ náßych do grobu 1985, ‘And certain of them which were with us went to the sepulchre’. This spatial meaning of the allative is frequent and is traditionally considered as the main one. Proximity, however, is determined by the context in the case of three dimensional Grounds, whereas with two-, one-dimensional or dimensionless Grounds it is deter-mined by the lexical meaning of the reference object. 1.3. Animate Goal of motion. The Figure acquires a location in the physical sphere of the person, e.g. John 1,11: Sawúmpiump atêio / ir ſáwíeii io ne priéme 434, Do właſnośći prʒyßedł / á ſwoi go nie prʒyili 4219, ‘He came unto his own, and his own received him not’. 1.4. Goal of direction or orientation. The Figure is static. It is motivated by the transformations Figure’s motion towards Ground → Figure’s orientation towards Ground and Figure’s motion towards Ground → Figure’s extension towards Ground: ítieſeu iſúmṗ rkás ſawȧs 964, wyćigałem ku wam rce ſwoie 9716, ‘I have spread my arms towards you’. II. Non-spatial functions: 2. Purpose (purposes are destinations). This use type is very common. Allatives of this type correlate with the infinitive and dative of purpose. [žmonės] nêßa kríkßtoṗ S. maús waikęlús 34813, noßdo Chrʒtu świtego máłe ditki 35927, ‘People carry little children to baptize’. 3. Abstract Goal of motion (state or emotion). The Figure (a person) moves towards or into a psychological condition, e.g. John 13,20: Wiſſôkes nſſkurís piktái dáro nopkncʒe ßwieſós / ir notêiṫ ßwieſóſṕ 24036, ktory ʒle cyni / nienawidʒi świátłośći / y nie prʒychodʒi ná świátłość 24915, ‘For every one that doeth evil hateth the light, neither cometh to the light’. 4. Addressee, e.g. Luke 1,34: Táre taḋ Mariá Angełoṕ 4389, Rʒekłá tedy Márya do Anyołá 4547f, ‘Then said Mary unto the angel’. 5. Emotional target. The Figure (emotion) is directed to a Ground (a person, God, or an inanimate object). 6. Additive allative: Néſstoṗ purwóṗ êmes / sîłgiwâtos primâiße 4064, do tego błotá iemſkiego / śiływotnprʒymießał 42011, ‘Power of life was added to the mud of the Earth’. 7. Standard of comparison. With prilyginti ‘equate’, pridėti ‘add’ the allative is used as the standard of comparative constructions. 8. Possessor. With užgulėti, prigulėti, prieitis ‘belong, fit’ (Polish należeć) the allative is almost exclusively used with inanimate possessors. 9. Discourse organizing type. With eiti ‘go’, prieiti(s) ‘approach’, sugrįžti ‘return’ the allative denotes the topic of the discourse: Bęt’ ſugrßkimę Siméonoṗ 43013, Ale ſiwroćmy do Symeoná 44528, ‘Let’s go back to Simon’. 10. Allative of time (time is space). Usually the allative denotes a border of time approached by the Figure. 11. Recipient. With atsiųsti ‘send’, atnešti, nunešti ‘bring’, nešiojimas ‘bearing’ the allative is a person-recipient. 12. Benefactive. The allative is not a clearly spatial case. Though its local meaning constitutes almost a quarter of the instances, it is quite heterogeneous: four spatial functions are distinguished. The schematic meaning of the allative can be defined as Goal. This motivates the vast majority of its abstract functions. The traditional meaning of proximity is not fundamental for the allative; it is determined by the context and the lexical meaning of the reference object.